Exploration of the Use of Online Learning Applications to Improve Students' Mathematical Problem Solving - Sugestiana, Sugestiana; Stevens, Ken (HAMKA INSIGHT, 2023)
This study aims to find out the exploration of the use of online learning applications in learning and learning strategies. Mathematics is one of the important lessons, because in studying mathematics students are expected to not only understand the material being taught but also understand and can be applied in everyday life. Mathematical problem solving ability is one of the most important skills involved in learning mathematics. The teacher's role in learning mathematics is very important because it relates to learning strategies that can be used in the teaching and learning process. This research uses descriptive qualitative research. The technique of taking the subject in this study used the Purposive Sampling Technique. Exploration of the use of online learning applications in learning mathematics and learning strategies can be done in various ways, namely by conditioning fun and interactive learning and teachers can develop learning with Project Based Learning models that which can facilitate students to investigate, solve a mathematical problem, is student center and can produce a real work or product from the results of the project.